Proceedings International Parallel and Distributed Processing Symposium
DOI: 10.1109/ipdps.2003.1213154
|View full text |Cite
|
Sign up to set email alerts
|

The maximal utilization of processor co-allocation in multicluster systems

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
0
22
0
3
Order By: Relevance
“…One of the most important findings is that when the slowdown of jobs due to the wide-area communication is less than or equal to 1:25, it pays to use co-allocation. In [5], we consider the maximal utilization, i.e., the utilization at which the system becomes saturated, as a metric for assessing the performance of processor coallocation. …”
Section: Related Workmentioning
confidence: 99%
“…One of the most important findings is that when the slowdown of jobs due to the wide-area communication is less than or equal to 1:25, it pays to use co-allocation. In [5], we consider the maximal utilization, i.e., the utilization at which the system becomes saturated, as a metric for assessing the performance of processor coallocation. …”
Section: Related Workmentioning
confidence: 99%
“…Basically, the CF policy tries to reduce the overhead of waiting in multiple clusters for input files to become available in the right locations. We have performed comparison experiments of CF with the Worst-Fit (WF) jobplacement policy, which is the default policy of KOALA, whose aim is to keep the loads in the clusters balanced [7]. The results showed that the combination of the CF policy and file replication is very beneficial when jobs have large input files (i.e., larger than 2GB).…”
Section: Introductionmentioning
confidence: 99%
“…As grid technologies gain in popularity, separate clusters are increasingly being interconnected to create multicluster computing architectures for the processing of scientific and commercial applications [1][2] [5]. These constituent clusters may be located within a single organization or across different geographical sites [3] [6].…”
Section: Introductionmentioning
confidence: 99%